2021
DOI: 10.1590/fst.26220
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of carrageenan from Eucheuma spinosum using ohmic heating: optimization of extraction conditions using response surface methodology

Abstract: Seaweed is an important global commodity since it is the source of many important products such as carrageenans, agar, alginates, and bioactive compounds. Seaweed processing is an energy intensive process since it involves heating large volumes of seaweeds in alkali solutions at high temperatures for up to six hours. To increase energy efficiency, an ohmic based processing system has been developed but has not been tested thoroughly. Therefore, the objective of this study was to identify optimum processing con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…When they are mixed in the same water environment, the state characteristics of the composite system composed of polysaccharides and proteins are related to the interaction between them (Alfaris et al, 2022;Georgilis et al, 2020;Bartlová et al, 2021). With more and more in-depth research on polysaccharide/protein complexes, we found that the interaction between polysaccharides and proteins will affect the structure and stability of the composite system (Hasizah et al, 2021;Luo et al, 2022). Among them, mutual attraction and mutual repulsion were the main interaction modes, and they were affected by factors such as the composite ratio, pH, ionic strength, and temperature of the composite system (Xu et al, 2020).…”
Section: Introductionmentioning
confidence: 85%
“…When they are mixed in the same water environment, the state characteristics of the composite system composed of polysaccharides and proteins are related to the interaction between them (Alfaris et al, 2022;Georgilis et al, 2020;Bartlová et al, 2021). With more and more in-depth research on polysaccharide/protein complexes, we found that the interaction between polysaccharides and proteins will affect the structure and stability of the composite system (Hasizah et al, 2021;Luo et al, 2022). Among them, mutual attraction and mutual repulsion were the main interaction modes, and they were affected by factors such as the composite ratio, pH, ionic strength, and temperature of the composite system (Xu et al, 2020).…”
Section: Introductionmentioning
confidence: 85%